2002
DOI: 10.1056/nejmoa013029
|View full text |Cite|
|
Sign up to set email alerts
|

Amiodarone as Compared with Lidocaine for Shock-Resistant Ventricular Fibrillation

Abstract: As compared with lidocaine, amiodarone leads to substantially higher rates of survival to hospital admission in patients with shock-resistant out-of-hospital ventricular fibrillation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
302
2
32

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 691 publications
(339 citation statements)
references
References 14 publications
3
302
2
32
Order By: Relevance
“…For the important outcome of survival to hospital admission, there was very-low-quality evidence (downgraded for risk of bias, indirectness, and imprecision) from 1 RCT in adult OHCA 63 showing improved survival to hospital admission with intravenous amiodarone compared with intravenous lidocaine (OR, 2.17; 95% CI, 1.21-3.83; P=0.009).…”
Section: Consensus On Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…For the important outcome of survival to hospital admission, there was very-low-quality evidence (downgraded for risk of bias, indirectness, and imprecision) from 1 RCT in adult OHCA 63 showing improved survival to hospital admission with intravenous amiodarone compared with intravenous lidocaine (OR, 2.17; 95% CI, 1.21-3.83; P=0.009).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…For the important outcome of ROSC, there was very-lowquality evidence (downgraded for risk of bias, imprecision, indirectness, and possible publication bias) from 1 observational cohort study of pediatric IHCA 62 For the important outcome of survival to hospital admission, there was very-low-quality evidence (downgraded for risk of bias, indirectness, and imprecision) from 1 RCT in adult OHCA 63 showing improved survival to hospital admission with intravenous amiodarone compared with intravenous lidocaine (OR, 2.17; 95% CI, 1.21-3.83; P=0.009).…”
Section: Consensus On Sciencementioning
confidence: 99%
“…As discussed previously, amiodarone was compared to lidocaine in the treatment of out-of-hospital ventricular fibrillation in the ALIVE trial and found to lead to substantially higher rates of survival to hospital admission [36].…”
Section: Class III Antiarrhythmic Medications Amiodaronementioning
confidence: 99%
“…In a randomized trial, ALIVE, comparing lidocaine to amiodarone as an adjunct to defibrillation in patients with out of hospital cardiac arrest, there was significantly increased surivial to hospital admission with amiodarone when compared to lidocaine (23% vs. 12%) [36], Ohshige et al looked at use of lidocaine and epinephrine vs. epinephrine alone in patients with VF who experienced out of hospital cardiac arrest and found improved survival to discharge [37]. A similar study also found the use of lidocaine to improve chance of survival to hospitalization after out of hospital cardiac arrest with VF (38% vs. 18%), however, they did not find an improvement in survival until discharge.…”
Section: Class Ib Antiarrhythmic Medications Lidocainementioning
confidence: 99%
“…For the important outcome of ROSC, there was very-low-quality evidence (downgraded for risk of bias, imprecision, indirectness, and possible publication bias) from 1 observational cohort study of pediatric IHCA 62 For the important outcome of survival to hospital admission, there was verylow-quality evidence (downgraded for risk of bias, indirectness, and imprecision) from 1 RCT in adult OHCA 63 showing improved survival to hospital admission with intravenous amiodarone compared with intravenous lidocaine (OR, 2.17; 95% CI, 1.21-3.83; P50.009).…”
Section: Consensus On Sciencementioning
confidence: 99%